Argumentation and mathematical communication in textbooks for the eighth grade of primary education - Sebastián Collyer-Sáez; Emilio Castro-Navarro; Danilo Díaz-Levicoy (LPMPP Universitas Negeri Yogyakarta, 2023)
The purpose of this article is to characterise the questions that focus on the ability to argue and communicate in textbooks, from the curricular perspective and the Krummheuer’s model. For this, we carried out a content analysis by applying two checklists to the students' texts, the teacher's teaching guide, and the students' workbook for the 8th grade of basic school in Chile. After the analysis of 50 activities, we found that the questions that focus on the ability to argue and communicate lack collaborative work. This means the students assume a passive role within the work involving skill, since they work alone, without the necessary in-teraction to generate the development of the skill. It is also evident that the Krummheuer’s model complies with developing this skill, however, elements of the Toulmin Model -qualifiers and rebuttal- appear, which makes the process and work with this skill more complex and complete than is believed. Finally, it is necessary to alter the teaching guide, since it does not develop guide-lines on how teachers should work with the argue and communicate skills in the classroom.